The The Influence of Perceived Food Quality, Price Fairness, Perceived Value and Statisfaction on Customers’ Revisit and Word-of-Mouth on Cake & Bakery Shops In Yogyakarta and Surakarta - Haya Wijayantiarni, Fadia; Roostika, Ratna (Selekta Manajemen: Jurnal Mahasiswa Bisnis & Manajemen, 2022)
This research aims to examine and analyze the effect of perceived food quality, price fairness, perceived value perception, satisfaction on customers revisit and word of mouth on cake & bakery consumers in Yogyakarta and Surakarta. Model and hypothesis testing have been tested using a sample of 250 respondents with a population from cake & bakery visitors in the Yogyakarta and Surakarta areas. The sampling technique used is purposive sampling. The Structural Equation Modeling (SEM) method used to test the research model is AMOS version 24. The data variables used in this case include perceived food quality, price fairness, perceived value, satisfaction, customers revisit and word-of-mouth intentions. The model built eight hypotheses. Based on the results of the study, it is shown that the perceived food quality has a positive effect on price fairness, perceived value, and satisfaction.Price fairness has no effect on perceived value and price fairness has a positive effect on visitor satisfaction.Perceived value has a positive effect on satisfaction. Satisfaction has a positive effect on revisit and word-of-mouth intentions.